Aquaculture production and trade world wide survey - Josupeit H. (Aspects économiques de la production aquacole, 1995)
The paper covers the major trends in world aquaculture production during the past decade. The impact of increasing aquaculture production on world trade is discussed in detail for shrimp, salmon, sea bass and sea bream.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)